Nematode parasites of two anuran species Rhinella schneideri (Bufonidae) and Scinax acuminatus (Hylidae) from Corrientes, Argentina - Elizabeth González, Cinthya (2008)
The nematological fauna of most anuran species from Corrientes province, north of Argentina; has not been studied. We report for the first time the nematode species found in Rhinella schneideri and Scinax acuminatus. Forty four amphibians representing two species (R. schneideri -six males, three females and two juveniles- and S. acuminatus -fifteen males and eighteen females) were collected near the city of Corrientes, between January 2002 and December 2003 and searched for nematodes. R. schneideri contained eight species of nematodes (adults: Rhabdias füelleborni, R. elegans, Oswaldocruzia proencai, Cosmocerca podicipinus, C. parva and Falcaustra mascula; larvae: Porrocaecum sp. and Physaloptera sp.), and S. acuminatus contained three (adults: Cosmocerca parva and Oxyascaris caudacutus; larvae: Physaloptera sp.). We present morphology (scanning electron microscope) and metric information, range extensions, and new host records for these nematode species.